2017
DOI: 10.1039/c7cp07155h
|View full text |Cite
|
Sign up to set email alerts
|

How the hydrogen sorption properties of palladium are modified through interaction with iridium

Abstract: Hydrogen sorption (adsorption/absorption) in metals, in the form of thin films or nanoparticles, is a key process in the fields of energy storage and heterogeneous catalysis. Atomic hydrogen dissolved in the subsurface of a metal affects its surface atomic and electronic structures, and thereby its surface reactivity and catalytic properties. In addition, alloy effects modify both catalytic and hydrogen sorption phenomena. In order to rationalize recent experimental results showing the negative impact of hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Beyond downsizing, nanoalloying is an additional way of boosting the hydrogen absorption capacity, as shown for Pd-Pt and Ag-Rh systems [160]. In contrast, we have found that nanoalloying Pd with Ir strongly decreases the hydrogen absorption capacity of Pd and suppresses β hydriding [161,162] through the formation of a core-shell Ir@Pd structure (Figure 7, left-hand side) [163,164]. The decreased hydrogen capacity is correlated to a strongly increased preferential CO oxidation activity in the presence of H 2 (PROX process) with respect to pure Pd and Ir counterparts [161,165].…”
Section: Hydrogen Absorption and Hydridingmentioning
confidence: 70%
“…Beyond downsizing, nanoalloying is an additional way of boosting the hydrogen absorption capacity, as shown for Pd-Pt and Ag-Rh systems [160]. In contrast, we have found that nanoalloying Pd with Ir strongly decreases the hydrogen absorption capacity of Pd and suppresses β hydriding [161,162] through the formation of a core-shell Ir@Pd structure (Figure 7, left-hand side) [163,164]. The decreased hydrogen capacity is correlated to a strongly increased preferential CO oxidation activity in the presence of H 2 (PROX process) with respect to pure Pd and Ir counterparts [161,165].…”
Section: Hydrogen Absorption and Hydridingmentioning
confidence: 70%
“…[ 84 ] A DFT analysis in the Pd‐Ir system was performed to describe the hydrogen‐metal interaction which was weakened by the presence of iridium. [ 85 ] The influence of the particle structure and internal elemental distribution was approached both experimentally and theoretically (by DFT simulations) on Pt‐Au nanoparticles (7 nm), and compositions with a maximum catalytic efficiency were identified on the basis of the surface atom arrangement. [ 86 ] The strain inside nanoparticles was decisive for the catalytic performance in electrocatalysis.…”
Section: Application Of Bimetallic Nanoparticles In Heterogeneous Catmentioning
confidence: 99%
“…Thus, hydrogen bonding is weaker in our bimetallic PdIr/C catalysts than in the Pd/C. The recent DFT studies found a significant weakening of the strength of hydrogen bonding in the model system consisting of the Pd atomic layer deposited on the Ir(1 1 1) substrate ascribed to a downshift of the palladium d-band center due to the Ir-species [62]. For the pseudomorphic Pd monolayer on the crystalline Ir substrate, Kibller et al [64] measured negatively shifted hydrogen desorption peak potential by ca.…”
Section: Characterizationmentioning
confidence: 67%
“…Computational studies [61][62][63] have predicted that a Pd overlayer or Pd alloyed into the first layer of Ir(1 1 1) will show a decreased d-band center energy by ca. 0.4-0.73 eV, relative to pure Pd, which resulted in the experimentally determined weaker adsorption strength of small molecules like CO, H 2 [64].…”
Section: Xps Studiesmentioning
confidence: 99%